Moderation-Based Islamic Character Education Integrated into the Elementary School Curriculum - Masdul, Muhammad Rizal; Tang, Muhammad; Kuliawati; Rahmawati; Alwalid, Mohammed Alghiffar (LETIGES, 2026)
This research examines the implementation of a character education program based on moderation at MI Muhammadiyah Al-Haq Palu, where elementary students demonstrate measurable understanding of tolerance, balance, justice, and anti-violence values. The study investigates how curriculum design and multi-method teaching strategies integrate moderation values and identifies the determinants of student character development. Employing a qualitative instrumental case study design within a constructivist paradigm, data were collected through semi-structured interviews, Classroom observations, and document analysis, and analyzed using Miles, Huberman, and Saldaña's interactive thematic coding model, with triangulation to ensure trustworthiness. Six thematic factors emerged inductively from the data: teacher quality and commitment, visionary leadership, coherent curriculum design, family partnerships, favorable post-conflict local context, and institutional backing from Muhammadiyah. The multi-method pedagogical approach, combining interactive dialogic teaching, habituation practices, and inclusive environment design, addresses cognitive, behavioral, affective, and social dimensions simultaneously, supporting the progressive internalization of moderation values. These findings offer contextual evidence relevant to SDG 4.7 on education for global citizenship and appreciation of cultural diversity, and to SDG 16 on peaceful and inclusive societies through its focus on anti-extremism and coexistence education. As a single-site qualitative case study, findings are context-specific and intended to inform rather than prescribe broader practice.